Evaluasi Implementasi Manajemen Fasilitas dan Keselamatan di Rumah Sakit Jiwa Mutiara Sukma Provinsi NTB Menggunakan Pendekatan PDSA (Plan-Do-Study-Act) Tahun 2023 - Haryandi, Halid; Menap, Menap; Karjono, Karjono (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aims to evaluate the implementation of Facility and Safety Management (MFK) at the Mutiara Sukma Mental Hospital (RSJ). This type of research is qualitative research with a descriptive approach. The informants for this research are MFK implementers, namely the K3 committee/installation, management, structural officials and visitors. Data collection was carried out using in-depth interviews. Examination of the trustworthiness of the data in this research includes credibility and dependability. Data analysis uses the thematic analysis model. The result of this research is that the evaluation of MFK implementation at the Mutiara Sukma Mental Hospital (RSJ) is less active in involving K3 installations in the planning process up to the evaluation. Implementation of Facilities and Safety Management (MFK) can run well if there is a clear priority scale and results that can be measured according to targets. It is necessary to improve the implementation and socialization of programs, such as the Hospital Disaster Plan, Contractor Safety Management, and fire protection systems that need to be identified and periodically evaluated for the security and safety of all those in the hospital environment. The four phases in the PDSA cycle have not run optimally. Increasing human resource capacity, managerial commitment, K3 structure and clarity of funding sources are still obstacles. Collaboration between K3 installations and policy makers is needed to reformulate improvements to the implementation of Facility and Safety Management (MFK).